2011
DOI: 10.1177/1741826710393994
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary exercise testing and prognosis in heart failure due to systolic left ventricular dysfunction: a validation study of the European Society of Cardiology Guidelines and Recommendations (2008) and further developments

Abstract: We evaluated the longest list of CPET prognostic parameters yet studied in HF: ESC-predictors were independent predictors of cardiovascular events, and the ESC prototype showed a convincing predictive capacity, whereas none of 11 S-predictors enhanced the prognostic performance, except peak SBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 37 publications
1
29
0
3
Order By: Relevance
“…In HF, a RQ ratio >1.05 is considered as an indication of a significant effort by the patient. 30 Several prognostic studies in HF have considered CPET data as relevant, 13,14,18,23,31,32 including VO 2 at AT. [9][10][11][12][13][14][15][16][17]31 In the present study, we confirmed this finding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In HF, a RQ ratio >1.05 is considered as an indication of a significant effort by the patient. 30 Several prognostic studies in HF have considered CPET data as relevant, 13,14,18,23,31,32 including VO 2 at AT. [9][10][11][12][13][14][15][16][17]31 In the present study, we confirmed this finding.…”
Section: Discussionmentioning
confidence: 99%
“…From a clinical point of view, the value of oxygen uptake (VO 2 ) at AT is used for grading the severity of HF or the effects of therapy, or to assess cardiovascular risk in case of surgery, [9][10][11][12][13][14][15][16][17][18] and it has been proposed as an alternative to peak VO 2 , being it independent of patients' motivation, exercise protocol, and exercise duration. 19 However, even in the presence of anaerobic metabolism, AT is not identified in a large number of patients with HF.…”
Section: Clinical Perspective On P 987mentioning
confidence: 99%
“…С другой стороны, если АГ сопутствует нарушение сердечной функции и недостаточное увеличение сердечного выброса при физической нагрузке, то прогностическое значение АД во время физической нагрузки может пропадать [129]. Нако-нец, более высокое АД при физической нагрузке может сопровождаться даже лучшим прогнозом, например, как это имеет место у лиц в возрасте 75 лет [132], у пациентов с подозрением на заболева-ния сердца [133] или с сердечной недостаточностью [134], у которых более высокое АД при нагрузке говорит об относительно сохранной систолической функции сердца [125]. В заключение следует отме-тить, что совокупность имеющихся данных ставит под вопрос клиническую целесообразность измере-ния АД в пробах с физической нагрузкой в диагно-стических и прогностических целях у больных АГ.…”
Section: центральное артериальное давлениеunclassified
“…Należy wreszcie zauważyć, że wyższe BP podczas wysiłku może się nawet wiązać z lepszym rokowaniem, np. u osób w wieku 75 lat [132], u pacjentów z podejrzeniem choroby serca [133] lub u chorych z niewydolnością serca [134], u któ-rych wyższe BP podczas wysiłku wskazuje na relatywnie zachowaną czynność skurczową serca [125]. Reasumując, można uznać, że powyższe wyniki podważają kliniczną przydatność pomiarów BP podczas próby wysiłkowej dla celów diagnostycznych i prognostycznych u pacjentów z nadciśnieniem tętniczym.…”
Section: Ciśnienie Tętnicze Podczas Wysiłku Fizycznego I Innych Testóunclassified